Akurasi Biopsi Aspirasi Jarum Halus untuk Diagnostik Tumor Kelenjar Liur di RSUD DR Saiful Anwar Malang 2018-2022 - Fitria Mayasari; Muhammad Luqman Fadli; Nia Kania (Jurnal Syntax Admiration, 2024)
Fine needle aspiration biopsy is accepted as a safe, reliable, minimally invasive, and cost-effective method. Fine needle aspiration biopsy aims to assist clinicians in handling patients. The purpose of this study is to evaluate the validity of fine needle aspiration biopsy as a diagnostic tool in salivary gland tumors compared to histopathological examination at Dr. Saiful Anwar Malang Hospital for the period of 2018-2022. Methods: Fine needle aspiration biopsy examination was performed before surgery, then compared with the results of histopathological examination after surgery as gold standard and retrospectively reviewed. Fine needle aspiration biopsy results and histopathological results are classified as neoplasm or non-neoplasm and benign or malignant. Validity is determined from sensitivity, specificity, positive conjecture value, negative conjecture value and accuracy. As a result, there were 33 cases of salivary gland tumors that met the inclusion criteria in the period 2018-2022 were reviewed, then classified into neoplasms or non-neoplasms and benign or malignant neoplasms. The sensitivity, specificity, accuracy, positive presumptive value, and negative presumptive value of cytological diagnosis of fine needle aspiration biopsy of salivary gland tumors for the neoplasm or non-neoplasm category were 93.1%, 100%, 93.9%, 100%, 66.7% and for the benign or malignant category 94.4%, 88.9%, 92.6%, 94.4%, 88.9%. This study shows that salivary gland fine needle aspiration biopsy cytology is a reliable and accurate diagnostic method for the diagnosis of salivary gland lesions. Conclusions: Fine needle aspiration biopsy is a useful method for diagnostics in salivary gland tumors but cannot replace histopathological examination as the gold standard for diagnostics.